2021
DOI: 10.1016/j.amjoto.2021.103044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on telemedicine practice patterns in outpatient otolaryngology

Abstract: Objective Otolaryngology is considered high risk for Coronavirus Disease 2019 (COVID-19) exposure and spread. This has led to a transition to telemedicine and directly impacts patient volume, evaluation and management practices. The objective of this study is to determine the impact of COVID-19 on patient characteristics in relation to outpatient attendance, ancillary testing, medical therapy, and surgical decision making. Methods A retrospective case series at an acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Xiong’s USA based study reported that patients whose primary language was not English or Spanish were significantly less likely to use remote consultations compared to those whose primary language was English or Spanish (OR 0.34 [95% CI 0.18 to 0.65]; p = 0.001), [ 50 ]. The percentage of patients whose primary language was not English decreased significantly with remote consultations (p<0.001) in the study by Franciosi [ 46 ] but Shehan [ 48 ] reported no significant differences between the groups in the primary languages spoken. Three studies found that those with a first language other than English were less likely to opt for remote consultations but those that did were more likely to choose a telephone consultation than a video consultation [ 37 , 44 , 54 ].…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Xiong’s USA based study reported that patients whose primary language was not English or Spanish were significantly less likely to use remote consultations compared to those whose primary language was English or Spanish (OR 0.34 [95% CI 0.18 to 0.65]; p = 0.001), [ 50 ]. The percentage of patients whose primary language was not English decreased significantly with remote consultations (p<0.001) in the study by Franciosi [ 46 ] but Shehan [ 48 ] reported no significant differences between the groups in the primary languages spoken. Three studies found that those with a first language other than English were less likely to opt for remote consultations but those that did were more likely to choose a telephone consultation than a video consultation [ 37 , 44 , 54 ].…”
Section: Resultsmentioning
confidence: 95%
“…A retrospective cohort study was the most frequent study design [ 31 , 36 41 , 44 , 45 , 47 , 49 , 55 ]. All but one study reported data on participants’ gender [ 49 ], with twenty reporting ethnicity data [ 31 33 , 35 42 , 44 46 , 48 51 , 53 , 55 ] and fifteen mean age [ 31 35 , 39 , 42 , 46 , 48 , 51 54 , 57 , 58 ] ( Table 2 ). Twenty one studies reported data from a single time period [ 31 34 , 36 , 37 , 39 , 40 , 42 44 , 47 , 49 , 52 59 ], and eight reported a comparison of remote consultation uptake rates across two time periods [ 35 , 38 , 41 , 45 , 46 , 48 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations